WOMEN'S ECONOMIC ACTIVITY AND THE CONCEPT OF HUMAN DIGNITY: A SOCIO-PHILOSOPHICAL APPROACH (Modern American Journal of Social Sciences and Humanities, 2026)
This article examines the relationship between women's economic activity and the concept of human dignity from a socio-philosophical perspective. The study analyzes women's participation in economic processes as a multidimensional phenomenon associated with freedom, self-realization, social inclusion, justice, and sustainable development. Particular attention is paid to the experience of Uzbekistan, where enhancing women's economic opportunities has become one of the key priorities of social modernization and human-centered reforms. Employing ontological, axiological, and praxeological approaches, the research investigates the philosophical foundations of women's economic activity and its contribution to the realization of human dignity. The findings indicate that women's economic participation not only strengthens economic development but also expands individual capabilities, promotes social justice, and contributes to social stability. A conceptual model explaining the interaction between economic activity and human dignity is proposed.